Mixing Ability of Intercropped Wheat Varieties: Stability Across Environments and Tester Legume Species - Moutier, N.; Baranger, A.; Fall, S.; Hanocq, E.; Marget, P.; Floriot, M.; Gauffreteau, A. (Frontiers in Plant Science, 2022)
Cereals-legumes intercrops are developing mainly in low input or organic farming systems because of the over yielding and the numerous ecosystem services they provide. For this management, little advice is available for varietal choice and there is almost no specific breeding programs. Our study aimed to evaluate the mixing ability of a panel of bread wheat genotypes in intercropping and to assess the impact of environment and legume tester choice on this mixing ability. We used Land Equivalent Ratios (LER) to assess the mixing ability of a genotype defined as the combination of its ability to maintain its own yield in intercropping (Producer effect, LERw) and to let the mixed species produce (Associate effect, LERl). 8 wheat genotypes and 5 legume testers varieties were grown in sole crop and in all binary intercrops in 9 contrasting environments. Mixed model was used to evaluate the effects of wheat genotypes, legume testers, environments and all the interactions between these 3 factors on LERw and LERl. The selected wheat genotypes presented contrasting mixing ability, either in terms of Producer effect or Associate effect. The impact of the environment on those Producer and Associate effects is limited and similar between genotypes. However, a strong negative correlation was observed between those two components of the genotype mixing ability, an increase in Producer effect being generally associated with a similar decrease in Associate effect, except for three genotypes. The legume tester had also a significant effect on both LERw and LERl and on the Producer or Associate effects of wheat genotypes, making the choice of this tester particularly important. The 5 testers showed no significant differences in wheat genotype ordering for both their Producer or Associate effects. However, testers showed different competitivity and ability to discriminate genotypes: faba bean was very competitive, resulting in low LERt and a low capacity to discriminate wheat genotypes for their mixing ability. On the contrary, pea was less competitive, resulting in higher LERt and a better capacity to discriminate wheat genotypes. In particular, the Hr varieties (Geronimo and, in a lesser extent, Spencer) allowed to discriminate the most genotypes